2019
DOI: 10.1088/1361-6579/aafa8e
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal resection of a porcine model under thermographic monitoring

Abstract: One of the standard procedures in gastrointestinal surgery is bowel part resection, which can be necessary for various reasons, such as an occurrence of a tumour. To perform this type of surgery successfully, tissue blood flow must be evaluated very clearly.Commonly, the most frequently used technique is the surgeon observing and making a macroscopic evaluation of intestine blood flow. Another approach is to use the indocyanine green (ICG) imaging method, which is sufficiently effective but quite expensive. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The relationship between thermographic data and circulatory parameters has attracted increasing interest worldwide, with several articles addressing this topic in recent years. 1319 Studies to evaluate the skin microcirculation in vessels with a diameter of less than 150 µm (arteries, veins, and small-caliber lymphatic vessels) reported that thermography is equivalent to established methods such as capillaroscopy, video-capillaroscopy, laser Doppler flowmetry, and transcutaneous oxygen measurement. 22…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between thermographic data and circulatory parameters has attracted increasing interest worldwide, with several articles addressing this topic in recent years. 1319 Studies to evaluate the skin microcirculation in vessels with a diameter of less than 150 µm (arteries, veins, and small-caliber lymphatic vessels) reported that thermography is equivalent to established methods such as capillaroscopy, video-capillaroscopy, laser Doppler flowmetry, and transcutaneous oxygen measurement. 22…”
Section: Discussionmentioning
confidence: 99%
“…One relevant study used infrared thermography for qualitative evaluation, comparing the contrast image obtained by injection of indocyanine green into the nutrition arteries (gold standard) with thermographic images during surgical resection of part of a pig’s intestine to determine the limit of good perfusion and to build intestinal anastomosis, and the findings demonstrated optimal correlation and reliability. 15 Near-infrared fluorescence imaging has potential utility in vascular surgery and might be of beneficial use in patients with PAD, making it feasible for skin perfusion assessment through either an intravenous or intra-arterial route. This method has a variety of indications in patients with PAD, including peripheral perfusion measurement for diagnosis, quality control in revascularization, and guidance in amputation surgery, but the cost of this system is high and the method is invasive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canine, swine, and murine models show that decreases in temperature in the burn wound site are associated with a higher burn degree (e.g., full-thickness) [ 18 ] and that this is also related to a poor prognosis when skin-grafting or free-flap surgeries are performed, due to vascular alterations [ 19 , 20 , 21 ]. Likewise, indocyanine green imaging and IRT were used to evaluate tissue blood flow in a porcine model of intestinal resection, and the authors found that IRT can differentiate well-blooded intestinal segments [ 22 ]. Moreover, IRT has been applied to determine skin transplant viability and wound healing progress [ 17 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%